Impact of shear wave elastography and attenuation imaging for predicting life-threatening event in patients with metabolic dysfunction-associated steatotic liver disease - Yudai Fujiwara; Hidekatsu Kuroda; Tamami Abe; Tomoaki Nagasawa; Ippeki Nakaya; Asami Ito; Takuya Watanabe; Kenji Yusa; Hiroki Sato; Akiko Suzuki; Kei Endo; Yuichi Yoshida; et al. (Scientific Reports)
Abstract We aimed to elucidate the value of ultrasound-based biomarkers for predicting the major life-threatening events in metabolic dysfunction-associated steatotic liver disease (MASLD). We established a prospective cohort of 279 patients who underwent two-dimensional shear wave elastography (2D-SWE), ultrasound-guided attenuation parameter (UGAP). An area under the curve analysis was performed to determine the cutoff values of liver stiffness measurements (LSM) by 2D-SWE and attenuation coefficient (AC) by UGAP for a moderate fibrosis and a moderate steatosis. We then classified the cohort into Groups A (low LSM and low AC), B (low LSM and high AC), C (high LSM and high AC), and D (high LSM and low AC). We compared the incidence of events between the groups, and estimated the hazard ratios (HRs) with 95% confidence intervals (CIs). The LSM and AC cut off values were 8.37 kPa and 0.62 dB/cm/MHz, respectively. The cumulative incidence rate in Groups A, B, C, and D were 11.2%, 12.2%, 29.5%, and 31.0%/5years, respectively (p < 0.05). LSM (HRs = 1.20, 95%CIs: 1.09–1.32, p < 0.01), and AC (HRs = 1.62, 95%CIs: 1.04–2.51, p = 0.03) were associated with life-threatening events. A combination of 2D-SWE and UGAP may help identify patients with MASLD at high risk for subsequent life-threatening events.